2009
DOI: 10.3329/uhj.v4i2.2070
|View full text |Cite
|
Sign up to set email alerts
|

Variation of adult admission and co-morbidity to general intensive care unit of BSMMU: Impact on outcome

Abstract: A retrospective study was done in ICU of BSMMU during January to June 2007 with a total number of 157 patients. Patients were included from this hospital and also from private hospitals. In accordance of the criteria for analysis a structured questionnaire was used whereas data obtain from hospital record sheets and file. We observed admission diagnosis, co-morbidities, length of stay, different procedures and overall outcome. Among 157 Patients age group of 61-70 yrs. constitutes the major proportion, which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
(10 reference statements)
1
4
0
Order By: Relevance
“…Different factors for ICU mortality which are usually reported sometimes found to be contradictory partly because of differences in statistical analyses [3]. Mortality is higher among more than 60 years age group and in males which is comparable with other similar studies [4,5].Sepsis was the main cause of death in our study though other few studies had shown Ischaemic heart disease as the prime cause [6,7].In our study respiratory and cardiovascular causes for mortalty are 14.7% and 10.9% respectively. In a similar previous study Dongre A et al (2016) and Paudel et al(2011) found 19.06%-17.51% &22.86%-22.86% respectively [8,9].In our study population maximum were from rural area(70.7%).…”
Section: Resultssupporting
confidence: 78%
“…Different factors for ICU mortality which are usually reported sometimes found to be contradictory partly because of differences in statistical analyses [3]. Mortality is higher among more than 60 years age group and in males which is comparable with other similar studies [4,5].Sepsis was the main cause of death in our study though other few studies had shown Ischaemic heart disease as the prime cause [6,7].In our study respiratory and cardiovascular causes for mortalty are 14.7% and 10.9% respectively. In a similar previous study Dongre A et al (2016) and Paudel et al(2011) found 19.06%-17.51% &22.86%-22.86% respectively [8,9].In our study population maximum were from rural area(70.7%).…”
Section: Resultssupporting
confidence: 78%
“…Naturally, the death rate among the geriatric patients was high (12.26%), and the male preponderance among the patients (2.41:1) and in the deceased (4.38:1) was comparable to other studies. [ 15 20 21 ] However, the death rate in pediatric group (2.39-2.56%) resulted in this study is imperfect, which is quite high in other studies. [ 22 23 ] Not including the neonates and infants treated in pediatric ICU was one of the limitations of this study.…”
Section: Discussionmentioning
confidence: 86%
“…However, medical patients are at the higher risk of hospital mortality (23% vs. 14% for operative admission) because of their greater severity of illness in terms of acute physiological derangement and un-optimized comorbidity. [ 15 17 ] One multicenter cross-sectional Japanese study also reported similarly that a number of medical cases were much higher (61.1%) and surgery cases admitted ICU and mortality rate in ICU was found 2.5 time higher than hospital morality rate. [ 25 ] The current study result may have been affected by the local conditions of the health system and medical treatment, diagnostic system, and many confounding factors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations